Incentive contracts and hedge fund management - James E. Hodder; Jens Carsten Jackwerth (University of Konstanz, Center of Finance and Econometrics (CoFE), 2005)
This paper investigates dynamically optimal risk-taking by an expected-utility maximizing manager of a hedge fund. We examine the effects of variations on a compensation structure that includes a percentage management fee, a performance incentive for exceeding a specified highwater mark, and managerial ownership of fund shares. In our basic model, there is an exogenous liquidation barrier where the fund is shut down due to poor performance. We also consider extensions where the manager can voluntarily choose to shut down the fund as well as to enhance the fund's Sharpe Ratio through additional effort. We find managerial risk-taking which differs considerably from the optimal risk-taking for a fund investor with the same utility function. In some portions of the state space, the manager takes extreme risks. In another area, she pursues a lock-in style strategy. Indeed, the manager's optimal behavior even results in a trimodal return distribution. We find that seemingly minor changes in the compensation structure can have major implications for risk-taking. Additionally, we are able to compare results from our more general model with those from several recent papers that turn out to be focused on differing parts of the larger picture.
urn:nbn:de:bsz:352-opus-17657
Keywords: 330; Investmentfonds; Hedging; Anlageverhalten; Führungskräfte; Vergütungssystem; Anreizvertrag; Theorie; Hedgefonds